Priority setting for Canadian Take-Home Naloxone best practice guideline development: an adapted online Delphi method - Ferguson, Max; Medley, Andrea; Rittenbach, Katherine; Brothers, Thomas D.; Strike, Carol; Ng, Justin; Leece, Pamela; Elton-Marshall, Tara; Ali, Farihah; Lorenzetti, Diane L.; Buxton, Jane A. (Université d'Ottawa | University of Ottawa, 2022)
Abstract Background Take-Home Naloxone (THN) is a core intervention aimed at addressing the toxic illicit opioid drug supply crisis. Although THN programs are available in all provinces and territories throughout Canada, there are currently no standardized guidelines for THN programs. The Delphi method is a tool for consensus building often used in policy development that allows for engagement of stakeholders. Methods We used an adapted anonymous online Delphi method to elicit priorities for a Canadian guideline on THN as a means of facilitating meaningful stakeholder engagement. A guideline development group generated a series of key questions that were then brought to a 15-member voting panel. The voting panel was comprised of people with lived and living experience of substance use, academics specializing in harm reduction, and clinicians and public health professionals from across Canada. Two rounds of voting were undertaken to score questions on importance for inclusion in the guideline. Results Nine questions that were identified as most important include what equipment should be in THN kits, whether there are important differences between intramuscular and intranasal naloxone administration, how stigma impacts access to distribution programs, how effective THN programs are at saving lives, what distribution models are most effective and equitable, storage considerations for naloxone in a community setting, the role of CPR and rescue breathing in overdose response, client preference of naloxone distribution program type, and what aftercare should be provided for people who respond to overdoses. Conclusions The Delphi method is an equitable consensus building process that generated priorities to guide guideline development.